Case studies of atmospheric moisture sources in the source region of the Yellow River from a Lagrangian perspective. (16th August 2021) - Liu, Rong; Wen, Jun; Wang, Xin; Wang, Zuoliang; Liu, Yu
Abstract: In this study, atmospheric moisture source regions and transport pathways, which substantially affect extreme summer precipitation events in the source region of the Yellow River (SRYR) of China were investigated using the Lagrangian Flexible Particle Dispersion Model (FLEXPART). Based on the 24‐hour cumulative precipitation data from the China Meteorological Data Service Center, 2012 and 2015 were selected to represent wet and dry years during the period 2007–2016, respectively. The results indicate that potential moisture sources include the northern Tibetan Plateau, the Bay of Bengal, the southern edge of the Himalayas, Sichuan Basin, and the SRYR. In the wet year, moisture from the southern branch was transported along two pathways: (a) moisture from the Arabian Sea was carried by the Somalia jet and entered the SRYR through the Indian Peninsula and Bay of Bengal, and (b) moisture from the South China Sea entered the SRYR through the Sichuan Basin. In the dry year, the moisture primary originated from the northern branch. Moisture from the eastern European Plain or northern Africa was carried by the westerly jet and entered the SRYR. It is estimated that the ratios of moisture from the northern and southern branches contributing to the precipitation in the SRYR were 22.1 and 15.9% in the wet year, while they were 52.9 and 8.4% in the dry year, respectively. Internal moisture recycling contributed 22.0% to precipitation in the wet year and 11.0% in the dry year. In this study, the transport trajectories of moisture contributing to extreme precipitation events in the SRYR are delineated. The results indicate that the northern branch is the primary contributor of moisture in the SRYR. Abstract : Location of the SRYR and monthly precipitation recorded at 11 meteorological stations from 2007 to 2016.